Black is the colour of my true love's heart eaudiobook Inspector felse mysteries series, book 6. - Peters, Ellis (The Felse Investigations, 2014)
Sparks fly when two famous folksingers and former lovers encounter each other at a folk music seminar. When one of them disappears, Dominic Felse and his girlfriend Tossa struggle to find an explanation. Although he doesn't know it, Dominic holds one of the most important clues to solving the mystery.